State of Maryland Education Management Information Systems : SABER Country Report 2015 - World Bank Group (World Bank, Washington, DC, 2016)
In 2011 the World Bank Group commenced a multiyear program designed to support countries in systematically examining and strengthening the performance of their education systems. Part of the World Bank’s new Education Sector Strategy, this evidence-based initiative, called SABER (Systems Approach for Better Education Results), uses diagnostic tools for examining education systems and their component policy domains against global standards and best practices and in comparison with the policies and practices of countries around the world. By leveraging this global knowledge, the SABER tools fill a gap in the availability of data and evidence on what matters most to improve the quality of education and achievement of better results. This report discusses the results of applying the SABER Education Management Information Systems (EMIS) tool in the State of Maryland in the United States. The objectives of this paper are twofold. First, it examines the system according to key policy areas, identifies successes and challenges in the system, and provides recommendations to support the continued advancement of EMIS in Maryland.